Parental unemployment and children's school performance - Anna Öster (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This study investigates the effect of parental unemployment on children's school performance. We use individual level data for all children completing lower secondary school in Sweden in 1990 directly moving on to three years of upper secondary school. We control for family and individual heterogeneity by means of lower secondary school GPA. The huge variation in Swedish unemployment during the beginning of the 1990s provides an ideal setting for testing the hypothesis that parental unemployment affects children's school performance. Our results indicate that having an unemployed father has a negative effect on children's school performance while having an unemployed mother has a positive effect.
Keywords: E24; I21; J12; 330; School performance; unemployment; Familie; Arbeitslosigkeit; Bildungsverhalten; Schweden